2023
DOI: 10.1186/s12944-023-01811-5
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between triglyceride-glucose index and aminotransferase among Royal Thai Army personnel 2017–2021: a serial cross-sectional study

Abstract: Background Insulin resistance (IR) is a major pathogenesis of nonalcoholic fatty liver disease (NAFLD). The triglyceride-glucose (TyG) index has recently gained popularity to assess IR and NAFLD due to its simplicity and low cost. The aim of the current study was to evaluate the relationship between the TyG index and aminotransferase. Methods A serial cross-sectional study was conducted among 232,235 Royal Thai Army (RTA) personnel aged 35–60 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Similarly, Ghorbani and colleagues, in their cross-sectional study, demonstrated that, with adjustments for confounding factors, the TyG index in individuals suffering from coronary artery disease (CAD) is connected to the greater chance of hyperuricemia (OR = 1.6, 95% CI: 1.02-2.51) [22]. In studies involving other regions and populations, similar conclusions have been reached [23,24]. Since hyperuricemia is a precursor to gout, the research noted a nonlinear constructive correlation associating the TyG index with increased likelihood of gout in the adjusted model.…”
Section: Discussionmentioning
confidence: 74%
“…Similarly, Ghorbani and colleagues, in their cross-sectional study, demonstrated that, with adjustments for confounding factors, the TyG index in individuals suffering from coronary artery disease (CAD) is connected to the greater chance of hyperuricemia (OR = 1.6, 95% CI: 1.02-2.51) [22]. In studies involving other regions and populations, similar conclusions have been reached [23,24]. Since hyperuricemia is a precursor to gout, the research noted a nonlinear constructive correlation associating the TyG index with increased likelihood of gout in the adjusted model.…”
Section: Discussionmentioning
confidence: 74%
“…In a recent study by Lertsakulbunlue et al, it was stated that a TyG index threshold of 8.89 for males and 8.57 for females could effectively predict elevated aminotransferase levels [ 15 ]. Accordingly, the present study unveiled similar TyG index edges of 8.88 for males and 8.54 for females as optimal cutoff points for identifying hyperuricemia.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity was defined as a BMI of at least 25 kg/m 2 [ 19 , 20 ]. Males with elevated AST or ALT levels below 40 U/L and females with elevated AST or ALT levels below 35 U/L were considered to have high levels [ 15 ]. The TyG index was computed using the equation ln [TG (mg/dL)*FBG (mg/dL)/2] [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation